2000
DOI: 10.2307/2657006
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Livistona chinensis var. subglobosa (Arecaceae) on the “islet of the gods”: Aoshima, Japan

Abstract: RAPD analysis was performed to discuss the origin of Livistona chinensis var. subglobosa using samples from eight localities, Iriomotejima, Ishigakijima, Okinawa, Yakushima, Tanegashima, Cape Sata, Tsukishima, and Aoshima, in Japan. Random amplified polymorphic DNA (RAPD) markers were obtained using five random primers and analyzed by the unweighted pair group method arithmetic (UPGMA). Data from Iriomotejima clustered with data from Aoshima, suggesting the possibility that seeds or green woods were carried by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Coastal plant species may differ from other terrestrial taxa because of their hydrochorous habit, wide geographic range and linear distribution along the coastal lines (Kadereit et al, 2005). Recent DNA marker-based studies of coastal plants have found taxa with both strong (Yoshida, 2000;Kadereit et al, 2005;Matsumura, 2009) and weak (Arafeh and Kadereit, 2006;Takayama et al, 2006) phylogeographic structuring. Kadereit and Westberg (2007) suggested that glacial histories, abiotic factors such as oceanic currents, and species-specific biology have all interwoven to yield their phylogeographic structures.…”
Section: Implications For the Colonization History And Pattern Of Oceanic Dispersalmentioning
confidence: 99%
See 1 more Smart Citation
“…Coastal plant species may differ from other terrestrial taxa because of their hydrochorous habit, wide geographic range and linear distribution along the coastal lines (Kadereit et al, 2005). Recent DNA marker-based studies of coastal plants have found taxa with both strong (Yoshida, 2000;Kadereit et al, 2005;Matsumura, 2009) and weak (Arafeh and Kadereit, 2006;Takayama et al, 2006) phylogeographic structuring. Kadereit and Westberg (2007) suggested that glacial histories, abiotic factors such as oceanic currents, and species-specific biology have all interwoven to yield their phylogeographic structures.…”
Section: Implications For the Colonization History And Pattern Of Oceanic Dispersalmentioning
confidence: 99%
“…For coastal and maritime floras, the KC had long been hypothesized to have brought the tropical elements suitable for dissemination by sea to the subtropical islands of the Ryukyus (Nakanishi, 1988;Kuo et al, 2006). These conjectures have been supported by molecular data recently (Yoshida et al, 2000;Matsumura et al, 2009). However, to our knowledge, the impacts of the KC on coastal plants in Taiwan have rarely been addressed in the recent literature.…”
Section: Introductionmentioning
confidence: 99%
“…Notes on general distribution: L. chinensis is native to Eastern Asia including China, Japan (i.e., Ryukyu Islands, Bonin Islands) and Taiwan (Horikawa 1972, Suzuki 1982, Yoshida et al 2000, USDA-ARS 2016. The species is widely cultivated as an ornamental and can be found naturalized in the West Indies, tropical America and on many islands in the Indian and Pacific Oceans (Wagner et al 1999, Meyer et al 2008, Flora of China Editorial Committee 2016, Govaerts 2016, PIER 2016.…”
Section: Analytical Key Of Genera Withinmentioning
confidence: 99%
“…A similar establishment of remote populations based on cultural uses by ancient people was also reported in a close relative, Livistona mariae , an endemic fan palm in arid central Australia (Kondo et al ; Bowman et al ). Although these hypotheses were examined with one remote population by random amplified polymorphic DNA (RAPD) analysis (Yoshida et al ), it remains unclear how remote populations became established in such regions because of the limited number of analyzed populations and the low level of polymorphism in RAPD analysis.…”
Section: Introductionmentioning
confidence: 99%